Intraventricular Extension of Supratentorial Intracerebral Hemorrhage: The Modified Graeb Scale Improves Outcome Prediction in Lund Stroke Register - Hansen, Björn M. (Neuroepidemiology, 2015)
BACKGROUND/AIMS: The modified Graeb Scale (mGS) is a semi-quantitative method to assess the extension of intraventricular hemorrhage (IVH) in patients with intracerebral hemorrhage (ICH). The mGS has been shown to prognosticate outcome after ICH in cohorts derived from convenience samples. We evaluated the external validity of mGS in supratentorial ICH-patients from an unselected cohort. METHODS: ICH-patients were included prospectively and consecutively in Lund Stroke Register. Follow-up survival status was obtained from the National Census Office; functional outcome was obtained from the Swedish Stroke Register or medical records. Using multivariate analyses, we examined if mGS was related to 30-day survival or poor functional outcome (modified Rankin Scale ≥ 4) at 90 days. RESULTS: Of 198 supratentorial ICH-patients, 86 (43%) had IVH (median mGS 12, range 1–28). In multivariate regression analyses, the mGS independently predicted 30-day mortality (per point; OR 1.16; 95% CI 1.06–1.27; p = 0.002) and poor functional outcome (OR 1.11; 95% CI 1.02–1.20; p = 0.011) after ICH. In receiver-operator characteristic analysis, the addition of mGS tended to be associated with a higher prognostic accuracy for survival (area under curve 0.886 vs. not including mGS 0.812; p = 0.053). CONCLUSIONS: The mGS improves outcome prediction after supratentorial ICH beyond other previously established factors in an unselected population.